The M6.9, 1980 Irpinia earthquake (southern Italy): joint surface ruptures dataset - Cecilia Martinelli; Daniela Pantosti; Francesca Romana Cinti; Riccardo Civico; Anna Maria Blumetti; Luca Guerrieri (PANGAEA, 2022)
This dataset gathers all the published existing information on the coseismic surface ruptures produced by the Mw 6.9 earthquake that struck the Irpinia region (southern Italy) on the 23rd November 1980. The dataset is the sum of the observations made by several authors over the years (e.g., Carmignani et al., 1981, Westaway and Jackson, 1984, Pantosti and Valensise, 1990, Blumetti et al., 2002). The data were collected during field surveys carried out from right after the event till 2021 and were integrated by aerial photo interpretation. The most recent surveys by the authors of this database were focused on the evaluation, repositioning through GNSS handheld devices, and validation in the field of the observation points to overcome unprecise manual positioning of pre-GNSS times. The observations are organized in a database of 175 homogenous georeferenced points and 49 georeferenced lines (coseismic ruptures). The points data are available in .xlsx meanwhile the lines are available in .shp format. Each point is described by the following parameters, when available: Observation type, Latitude, Longitude, Elevation, Throw, Strike, Dip, References, Ranking, Comment, and Bibliography. The ranking assigned to each coseismic feature is based, with integrations, on Baize et al. 2021. Each feature is attributed to two ranking values, one referring to the compilers of this database and the other to the original author extquotesingles interpretation. The scores are 1 to 4: 1) principal faulting; 2) simple distributed faulting; 3) sympathetic faulting; 4) ground shaking or shaking/gravity-induced slip (category assigned in this work). The lines are described by Type of observation, Uncertainty, Strike, Downthrow Side, Ranking, Comment, and Bibliography. The ranking values are the same as above. The downthrow side value for each line is the mode of the observation points located on the line itself. As a consequence of the different ages and origins of the data, including the variable scaling of the surveys, we have built the dataset at different scales; we suggest looking at the project at the scale spanning from 1:5.000 to 1:10.000.